Modelling of Annual Stream Flows by Autoregressive Models - Wagh, R N; Kumar, Devendra (Journal of Agricultural Engineering, 2006)
The main aim of the present study was to develop a autoregressive model for annual streamflow of Godavari river. Autoregressive models of order 1,2,3,4 and 5 were tried. AR (1) model was found suitable based on Box- Pierce Portmonteau test and Akaike Information Criterion test. The mean and skewness of generated series were found close to historical values. The mean forecast error. mean relative error and integral square error indicates a high degree of model fitness to the observed data series.